2005
DOI: 10.1016/s0917-2394(05)70024-0
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of sensing lower-jaw-position in patients with cerebral palsy during laughing gas-induced sedation

Abstract: To clarify the effects of the applied during sedation with nitrous oxide (hereafter referred to as laughing gas) on the ability of muscles attached to the lower jaw to sense lower-jaw-position and on the sensation of muscle spindles attached to the lower jaw in patients with cerebral palsy (CP) using healthy adult subjects without functional abnormalities of the jaws and oral cavities as control subjects (hereafter referred to as healthy subjects). Experiments were performed under the following conditions: for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Yoshida et al 21) investigated the effects of LG-induced sedation on muscle sensation accompanied by the extension of the muscles attached to the lower jaw in healthy subjects, and confirmed that the ability to discriminate LJP is decreased by LG. Yoshida et al 11) also investigated these effects in CP patients and confirmed that the ability to discriminate LJP is improved by LG. Furthermore, Yoshida et al 12) reported that the involuntary muscle tonus of the jaw-facial plane in CP patients is inhibited by the inhalation of nitrous oxide gas (hereafter referred to as laughing gas (LG)) during dental practice, on the basis of the frequency analyses of electromyographies.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…Yoshida et al 21) investigated the effects of LG-induced sedation on muscle sensation accompanied by the extension of the muscles attached to the lower jaw in healthy subjects, and confirmed that the ability to discriminate LJP is decreased by LG. Yoshida et al 11) also investigated these effects in CP patients and confirmed that the ability to discriminate LJP is improved by LG. Furthermore, Yoshida et al 12) reported that the involuntary muscle tonus of the jaw-facial plane in CP patients is inhibited by the inhalation of nitrous oxide gas (hereafter referred to as laughing gas (LG)) during dental practice, on the basis of the frequency analyses of electromyographies.…”
Section: Introductionmentioning
confidence: 88%
“…A measurement was performed after the stimulator was applied to the chin in the lower jaw of a subject for 3 s to provide vibration. Measurements were also performed before the inhalation of LG and oxygen (air-inhalation condition: hereafter referred to as without LG inhalation) and during the inhalation of LG and oxygen (condition of LG and oxygen inhalation under LG induced sedation: referred to as during LG inhalation) 11) . In a test of the ability to discriminate LJP during LG inhalation, measurements were begun when a subject exhibited the optimal sedation as described in Table 1 11,21) .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations